In vitro Susceptibility of Human Cell Lines Infection by Bovine Leukemia Virus - Olaya-Galán, Nury N.; Blume, Skyler; Tong, Kan; Shen, HuaMin; Gutierrez, Maria F.; Buehring, Gertrude C. (Frontiers in Microbiology, 2022)
Evidence of the presence of bovine leukemia virus (BLV) in human beings and its association with breast cancer has been published in the literature, proposing it as a zoonotic infection. However, not enough evidence exists about transmission pathways nor biological mechanisms in human beings. This study was aimed at gathering experimental evidence about susceptibility of human cell lines to BLV infection. Malignant and non-malignant human cell lines were co-cultured with BLV-infected FLK cells using a cell-to-cell model of infection. Infected human cell lines were harvested and cultured for three to six months to determine stability of infection. BLV detection was performed through liquid phase PCR and visualized through in situ PCR. Seven out of nine cell lines were susceptible to BLV infection as determined by at least one positive liquid-PCR result in the three-month culture period. iSLK and MCF7 cell lines were able to produce a stable infection throughout the three-month period, with both cytoplasmic and/or nuclear BLV-DNA visualized by IS-PCR. Our results support experimental evidence of BLV infection in humans by demonstrating the susceptibility of human cells to BLV infection, supporting the hypothesis of a natural transmission from cattle to humans.